Everyday Internationalism as an Educational Project: School Curriculum and Pedagogies for World-Mindedness. Issue 4 (2nd October 2019) - McLeod, Julie
ABSTRACT: This article examines education for internationalism during the interwar years, addressing curriculum initiatives in Australia with reference to reforms promoted by the League of Nations and progressive education networks. Two main questions are explored: First, how were the logics of interwar internationalism mobilised in educational debates in Australia? And second, how were such aspirations socialised beyond the pages of official exhortations and the visions of elites? Interwar internationalism relied heavily on the promise of educational endeavours to advance international understanding. Despite the declared importance of education in histories of internationalism, this article argues that insufficient weight has been given to the crucial role of school curriculum in recontextualising these ideals and putting them into practice. Curriculum has governmental, epistemic, normative and technical dimensions, and all were engaged in mediating internationalist sentiment. Analysing public debate and Australian school history textbooks and reports written by influential educator Alice Hoy, this article shows how curriculum worked to secure an idealised world-minded citizen and simultaneously embed dividing practices and hierarchies along racialised and civilisational lines. Finally, contemporary educational concerns about global citizenship are situated in a longer history of curriculum reforms that have generated powerful norms and exclusions in pursuit of world-minded future citizens.